Impact of the Global Crisison Banking Sector Soundness in Asian Low-Income Countries. (IMF Working Papers; Working Paper ;, 2011)
The paper takes stock of the impact of the global financial crisis that began in late 2007 on banking sectors of Asian low-income countries, by exploring bank-level data provided by Bankscope. The paper examines three key channels of possible crisis spillovers: exposures to (i) valuation changes of mark-to-market financial assets, (ii) a drop in crossborder funding, and (iii) rises in NPLs prompted by international real economic linkages. The paper finds that despite relatively low financial integration, the impact of the crisis on LIC banks, particularly the largest ones, were not insignificant. Impacts were most palpable through a loan-to-crossborder funding nexus.